The Impact of Long-Term Antibiotic Therapy of Cutaneous Adverse Reactions to EGFR Inhibitors in Colorectal Cancer Patients - Mihai, Mara Mădălina; Ion, Ana; Giurcăneanu, Călin; Nițipir, Cornelia; Popa, Ana-Maria; Chifiriuc, Mariana-Carmen; Popa, Mircea Ioan; Říčař, Jan; Popa, Liliana Gabriela; Sârbu, Ionela; Lazăr, Veronica (Journal of clinical medicine, 2021)
Colorectal cancer (CRC) is an important public health issue, in terms of incidence and mortality, with approximately 1.8 million new cases reported worldwide in 2018. Advancements in understanding pathophysiological key steps in CRC tumorigenesis have led to the development of new targeted therapies such as those based on epidermal growth factor receptor inhibitors (EGFR inhibitors). The cutaneous adverse reactions induced by EGFR inhibitors, particularly papulopustular rash, often require long-term antibiotic treatment with tetracycline agents (mostly minocycline and doxycycline). However, this raises several issues of concern: possible occurrence of gut dysbiosis in already vulnerable CRC patients, selection of highly antibiotic resistant and/or virulent clones, development of adverse reactions related to tetracyclines, interference of antibiotics with the response to oncologic therapy, with a negative impact on disease prognosis etc. In the context of scarce information regarding these issues and controversial opinions regarding the role of tetracyclines in patients under EGFR inhibitors, our aim was to perform a thorough literature review and discuss the main challenges raised by long-term use of tetracyclines in advanced CRC patients receiving this targeted therapy.
Keywords: gut microbiome dysbiosis; long-term antibiotic therapy; Fusobacterium nucleatum; acneiform rash; tetracyclines; EGFR inhibitors; papulo-pustular rash; metastatic colorectal cancer